A Content Analysis of Antibiotic use in Livestock in National U.S. Newspapers - Garrett M Steede; Courtney Meyers; Nan Li; Erica Irlbeck; Sherice Gearhart (Journal of Applied Communications, 2019)
The discovery of the antibiotic Aureomycin as a growth promotor for the livestock industry was viewed as revolutionary in 1950. The use of antibiotics as growth promoters in livestock, however, has been questioned by health professionals concerned with the role this use might play in the development of antibiotic resistant bacteria. As a public health issue, newspapers have covered this topic since its discovery. Media, such as newspapers, have used frames to discuss the topic over time as new discoveries have occurred, policy changes have been implemented, and food animal production has changed. The purpose of this study was to determine the frames and sources used by national U.S. newspapers when discussing the topic of antibiotic use in livestock and antibiotic resistance. A quantitative content analysis was conducted on three national U.S. newspapers from 1996 – 2017 and found three primary frames were used when discussing antibiotic use in livestock and antibiotic resistance. The content analysis also indicated that over 90% of the news articles contained a scientific source when communicating about this scientific topic. Based on the frames identified some readers are being ill-informed about this topic and could be using this information in their decision making without having all of the facts. Science communicators should prioritize the inclusion of scientific sources in their writing as they communicate about complex, controversial topics.
Keywords: Content Analysis; Livestock; Antibiotic; Newspaper; Framing